Results of observations to evaluate the impact of operational factors on the side rail wear - V. O. Pevzner; O. Y. Belotsvetova; A. V. Potapov (Вестник Научно-исследовательского института железнодорожного транспорта, 2016)
In 2012 - 2015 operational monitoring was carried out to evaluate intensity of lateral wear, depending on operating conditions in the curve of 350 m radius. The article presents data on the influence of operational factors on lateral wear of rails at the East Siberian, South-Ural and Privolzhskaya Railways. It is shown that the main factors affecting the lateral wear are: lubrication, rail canting, curve radius, the level of unbalanced acceleration. To manage the process of lateral wear and reduce its intensity the following should be made: elimination of multi-degree curves; maintaining rail canting within 1/16 - 1/27, thus the elimination of deviations in values of canting should be carried out by replacing the elastic under-rail and under-sleeper pads or by using standard leveling shims; providing well-known engineering solutions, such as design of curves with unbalanced acceleration in the range 0.3 m/s2 for freight and 0.7 m/s2 for passenger trains; lubrication of the rails in curved sections of the track.